1994
DOI: 10.1136/vr.135.13.304
|View full text |Cite
|
Sign up to set email alerts
|

Development of early bovine embryos in different culture systems

Abstract: The objective of this study was to examine the effects of different culture systems on the development of early bovine embryos in vitro. A total of 1089 oocytes were aspirated from 2 to 5 mm follicles of ovaries collected at a local abattoir; a high proportion of the oocytes matured in vitro were fertilised by spermatozoa capacitated with caffeine and heparin. Seven to eight hours after insemination, the oocytes were transferred into three in vitro systems: A, TCM 199 + 10 per cent fetal calf serum culture med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There were slight differences in the stage description of early embryonic development in the raccoon dog from other mammals. For example, mouse and pig embryos at the 16-cell stage are called "morula" (Patten, 1964;Yu, 1985), while greater than 8-cell embryos in human are also termed "morula" (Feng et al, 1994). We found that 16-cell embryos from the raccoon dog became compact.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There were slight differences in the stage description of early embryonic development in the raccoon dog from other mammals. For example, mouse and pig embryos at the 16-cell stage are called "morula" (Patten, 1964;Yu, 1985), while greater than 8-cell embryos in human are also termed "morula" (Feng et al, 1994). We found that 16-cell embryos from the raccoon dog became compact.…”
Section: Discussionmentioning
confidence: 90%
“…More importantly, there was a high percentage of degenerating eggs/embryos at 100-198 h after first mating, which coincided with the transition of 8-16 cell embryos from the oviduct to the uterus. This may be related to changes in the inner environment of the embryos or early embryonic developmental block happened like the arrested bovine embryos at the 8-16 cell stage (Feng et al, 1994;Toralova et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…The benefits of the granulosa co-culture system have been explored in bovine, 18,55 mouse, 50 human, 56,57 and sheep. 58 Overall, the results of the granulosa cell culture (regardless of species) suggest an enhancement of embryo quality and development to the blastocyst stage compared to standard culture conditions.…”
Section: Cumulus/granulosa Cellsmentioning
confidence: 99%
“…Mouse oocytes cultured in vitro with FSH demonstrate a dose-dependant effect on metaphase and prometaphase spindles (13). Bovine oocytes have also been proved to be matureable in vitro when supplied with gonadotropins, with maturation rates closely associated with gonadotropin concentrations (14,15). Some studies have creatively found ways to use animal model experiments, either in vitro or in vivo, to analyze the effects of gonadotropins on mammalian oocyte maturation (16)(17)(18)(19); this kind of research is expected to provide further support for their clinical application.…”
mentioning
confidence: 97%